Lane-free intersection control for connected automated vehicles prioritizing vulnerable road users - Malcolm, Patrick; Bogenberger, Klaus (Transportation research. Part C, Emerging technologies, 2025)
With the advent of connected autonomous vehicles (CAVs) come many possibilities for improving the capacity and level of service of roadways and intersections. Two such concepts are automated intersection management (AIM) and lane-free traffic. Previous research on lane-free AIM approaches is scant and often overlooks vulnerable road users (VRUs) such as pedestrians and cyclists. We present a novel first-come, first-served lane-free AIM algorithm specifically designed for urban environments and to give VRUs high priority. Simulation results show that our lane-free approach provides an excellent level of service for VRUs while also outperforming both a conventional traffic signal control design and a lane-based AIM approach with respect to CAV level of service, meaning that the deployment of lane-free AIMs could result in improved traffic flow for all road users while maintaining or reducing the amount of street space needing to be dedicated to vehicles. We also investigate the influence of the introduction of narrow vehicles and find that significant capacity improvements can be achieved with our lane-free approach even for relatively small market penetration rates. •Lane-free automated intersection management reduces vehicle delay at intersections.•Pedestrians and cyclists can also be served more efficiently and safely.•Lane-free traffic can reduce space required for urban vehicle infrastructure.